ChemInform Abstract: Lewis Acid Catalyzed Synthesis of Cyclic Carbonates, Precursors of 1, 2‐ and 1, 3‐Diols. Issue 8 (February 2015) - Cornil, Johan; Gonnard, Laurine; Guerinot, Amandine; Reymond, Sebastien; Cossy, Janine
Abstract The synthetic value of this method is demonstrated by total synthesis of alpinikatin (X).